PRINSIP HUKUM PROGRESIF SEBAGAI PARADIGMA PEMBAHARUAN SISTEM PERADILAN DI INDONESIA - Sastiono Kesek (Universitas Batanghari Jambi, 2014)
The principle of progressive law is the principle that has prospects can carry the scars bawdy world of law becomes the law of a more dignified and useful for social life and should serve as guidelines by the courts in order to ensure substantive justice for the community. Because the court's good or bad depends on the mindset and behavior of the judge. Judges who use the standard obligations of morality, the morality of critical sense and morality, conscience and spiritual intelligence in enacting hear the case then obviously it will be easier to provide justice for the people who seek justice.Progressive Law paradigm that prioritizes responsive law is supposed to be the main reference basis of the court in deciding a case not only based on the narrow procedural fairness alone. Responsive law largely embedded in the values adopted in the society as well as embedded in the public sense of justice in a region.Keywords: Progressive Law, Justice, Judge.